2016
DOI: 10.1007/s10787-016-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of AMPK signaling pathway in rat model of diabetic neuropathy

Abstract: Diabetic neuropathy (DN) is characterized as Hyperglycemia activates thdisturbed nerve conduction and progressive chronic pain. Inflammatory mediators, particularly cytokines, have a determinant role in the pathogenesis of neuropathic pain. The activity of adenosine monophosphate protein kinase (AMPK), an energy charge sensor with neuroprotective properties, is decreased in diabetes. It has been reported that activation of AMPK reduces the systemic inflammation through inhibition of cytokines. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 47 publications
5
35
0
Order By: Relevance
“…AMPK depletion has been linked to impaired axonal bioenergetic profile in diabetes (Roy Chowdhury et al, 2012). Moreover, the AMPK activator met-formin both protects nerve conduction and diminishes pro-inflammatory markers such as TNFα and plasma CRP in diabetic rats (Hasanvand et al, 2016) and we found similar effects of J147 on these indices of inflammation. While further studies are required to determine the precise neuroprotective mechanisms of J147 in diabetic neuropathy, efficacy of this curcumin derivative against MNCV slowing supports advancement to clinical investigation.…”
Section: Discussionsupporting
confidence: 66%
“…AMPK depletion has been linked to impaired axonal bioenergetic profile in diabetes (Roy Chowdhury et al, 2012). Moreover, the AMPK activator met-formin both protects nerve conduction and diminishes pro-inflammatory markers such as TNFα and plasma CRP in diabetic rats (Hasanvand et al, 2016) and we found similar effects of J147 on these indices of inflammation. While further studies are required to determine the precise neuroprotective mechanisms of J147 in diabetic neuropathy, efficacy of this curcumin derivative against MNCV slowing supports advancement to clinical investigation.…”
Section: Discussionsupporting
confidence: 66%
“…Kooy et al studied the effect of Metformin added to insulin therapy in 390 patients with type 2 DM and macro- and microvascular complications; they discovered that Metformin reduced macrovascular complications at 4.3 years of follow-up, although no beneficial effects on DPN were observed [126]. Recently, Hasanvand et al demonstrated that the activation of AMP kinase signaling pathway in diabetic neuropathy might be associated with the anti-inflammatory response, and Metformin reduced the levels of inflammatory cytokines in diabetic rats; it also improved motor nerve conduction velocities of the sciatic nerves [127]. …”
Section: Diabetic Polyneuropathymentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) activity plays a vital role in mediating hepatic lipogenesis[18]. Recent studies have shown that AMPK activity is reduced by the factors implicated in the development of NAFLD, such as inflammation and obesity[19,20]. Therefore, inhibition of hepatic lipogenesis by AMPK activation is envisaged as a viable therapeutic strategy to prevent the initiation and progression of NAFLD[21].…”
Section: Introductionmentioning
confidence: 99%